Chronic exposure to aflatoxin B1, ochratoxin A, and citrinin in women and children and associated health risk characterization: blood biomonitoring evidence from rural Bangladesh - Nicholas N. A. Kyei; Benedikt Cramer; Hans-Ulrich Humpf; Michael Kuhn; Shafinaz Sobhan; Jannik Veerkamp; Sabine Gabrysch (Environmental Health, 2026)
Abstract Dietary exposure to mycotoxins—including aflatoxins (AFs), ochratoxin A (OTA), and citrinin (CIT)—represents an important health risk, particularly in low-resource settings with widespread food contamination. This study investigates mycotoxin exposure among 719 participants (433 women and 286 children) of a cluster-randomized trial in rural Bangladesh, using residual blood samples collected during the 2019 endline survey. A total of 712 whole blood and 578 serum samples were analyzed by ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). Serum aflatoxin B1 (AFB 1 )-lysine adducts were quantified following enzymatic digestion and solid-phase extraction. To evaluate potential health risks, we estimated probable daily intake (PDI) from blood concentrations of frequently detected mycotoxins. All whole blood samples contained at least two mycotoxins, and 84% of participants were co-exposed to at least three mycotoxins. Biomarkers for the main blood-relevant mycotoxins were frequently detected, with OTA detected in 100% of whole blood samples and its isomer, 2′R-ochratoxin A (2′R-OTA), detected in 98%, CIT in 91%, and Enniatin B (EnB) in 92%, while AFB1-lysine—a biomarker of chronic exposure to the potent carcinogen AFB1—was detected in nearly one-quarter of women and 4% of children with serum samples. Beauvericin was detected in 6% of samples. The PDI of OTA exceeded health-based guidance values in 80% of women and 99% of children, while the PDI of CIT was of concern for 12% of women and 27% of children. These findings demonstrate widespread co-exposure to multiple mycotoxins, with OTA, CIT, and AFB 1 posing notable risks, underscoring the urgent need for targeted interventions to protect vulnerable populations.